Dual Transcriptomics of Host-Pathogen Interaction of Cystic Fibrosis Isolate Pseudomonas aeruginosa PASS1 With Zebrafish - Kumar, Sheemal S.; Tandberg, Julia I.; Penesyan, Anahit; Elbourne, Liam D. H.; Suarez-Bosche, Nadia; Don, Emily; Skadberg, Eline; Fenaroli, Federico; Cole, Nicholas; Winther-Larsen, Hanne Cecilie; Paulsen, Ian T. (Frontiers in Cellular and Infection Microbiology, 2018)
Pseudomonas aeruginosa is a significant cause of mortality in patients with cystic fibrosis (CF). To explore the interaction of the CF isolate P. aeruginosa PASS1 with the innate immune response, we have used Danio rerio (zebrafish) as an infection model. Confocal laser scanning microscopy (CLSM) enabled visualization of direct interactions between zebrafish macrophages and P. aeruginosa PASS1. Dual RNA-sequencing of host-pathogen was undertaken to profile RNA expression simultaneously in the pathogen and the host during P. aeruginosa infection. Following establishment of infection in zebrafish embryos with PASS1, 3 days post infection (dpi), there were 6739 genes found to be significantly differentially expressed in zebrafish and 176 genes in PASS1. A range of virulence genes were upregulated in PASS1, including genes encoding pyoverdine biosynthesis, flagellin, non-haemolytic phospholipase C, proteases, superoxide dismutase and fimbrial subunits. Additionally, iron and phosphate acquisition genes were upregulated in PASS1 cells in the zebrafish. Transcriptional changes in the host immune response genes highlighted phagocytosis as a key response mechanism to PASS1 infection. Transcriptional regulators of neutrophil and macrophage phagocytosis were upregulated alongside transcriptional regulators governing response to tissue injury, infection and inflammation. The zebrafish host showed significant downregulation of the ribosomal RNAs and other genes involved in translation, suggesting that protein translation in the host is affected by PASS1 infection.